Socio-demographic dimension of tourism development in Ukraine - Trunina, Iryna; Druzhynina, Viktoriia; Zahorianska, Olena; Pryakhina, Katerina (Społeczno-ekonomiczny wymiar rozwoju turystyki na Ukrainie, 2020)
Over the last decade, the tourism industry is considered to be an engine of economic development in many countries of the world. On the other hand, tourism as an important socio-economic phenomenon of modern times is closely related to the development of society and is subject to its laws, so the purpose of the research is defined as: the systematization of the existing approaches, identification and justification of the main socio-demographic factors for the development of the tourism industry in Ukraine against the backdrop of the world tourism industry. The scientific novelty: analysis of previous studies has identified the key demographic and social factors that have a direct impact and determine the main trends in tourism in Ukraine. The indirect social indicator for the level and quality of population life is determined as the disposable income per person; its comparative and retrospective analysis in the context of Ukrainian regions makes it possible to identify potentially promising areas for the development of tourism business with the existing demand from the local population
Biblioteka Regionalisty, 2020, Nr 20, s. 170-179
Keywords: population; demographic factors; social factors; tourism; transformation; ludność; czynniki demograficzne; czynniki społeczne; turystyka; transformacja; Ukraina; Ukraine